Earthquake-Induced Clot Layer - M. F. Orzimatova (Scientific Trends, 2023)
The article is devoted to the coverage of the research carried out on the study of the state of clots under strong dynamic (seismic) effects of the lyoss grunts on the floor of buildings and structures.
Keywords: seismic force, active layer, threshold, vibration speed, net weight.